(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Genre-Based Instructional Material (GB-IM) is an intervention material that uses the Genre-Based Approach (GBA) to improve the reading proficiency of Grade 7 students for School Year 2022-2023. It follows the four stages of the GBA Model which are: Building Knowledge of the Field (BKOF), Modeling of the Text (MOT), Joint Construction of the Text (JCOT), and Independent Construction of the Text (ICOT), and the design of Research and Development (R&D) by Gall and Borg. This study investigated the effects of Genre-Based Instructional Material (GB-IM) on the students’ reading proficiency. Specifically, it sought to determine the level of the teachers’ and students’ evaluation on the GB-IM, identify the reading proficiency level of the GB-IM and non-GB-IM groups in the pretest and post-test, ascertain if there is a significant difference in the evaluation of the teachers and students on the GB-IM, and assess if there is a significant difference between the pretest and posttest scores in the GB-IM and non-GB-IM groups. Results revealed that teachers and students had higher mean scores on the GB-IM evaluation. Moreover, the students’ proficiency level has a significant difference between the GB-SIM and Non-GB-SIM groups in their mean scores in the post-test results. Though both groups improved their scores, the GB-SIM group scored higher compared to the Non-GB-SIM group.